Tata Laksana Terintegrasi Sindrom Stevens-Johnson (SJS) dan Nekrolisis Epidermal Toksik (NET) - Dennely Yulisa; Sri Linuwih Menaldi (Cermin Dunia Kedokteran, 2023)
Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are acute life-threatening mucocutaneous reactions characterized by extensive epidermal necrosis and epidermal detachment. The incidence of SJS in Japan is 2.3 cases/100,000 people/per year. The mortality rate of SJS-TEN in Saudi Arabia is 1 per 10 cases (10%). SJS-TEN can be caused by drugs, idiopathic, infection, post-bone marrow transplant, immunization, radiotherapy, and genetics. The pathogenesis of SJS-TEN is suspected as a result of a cytotoxic reaction to keratinocyte cells which causes massive apoptosis. Clinical manifestation begins with prodromal symptoms followed by erythematous macular lesions and atypical target lesions that may confluence, then develop into bullous, oozing erosions with mucosal involvement. Vital sign observation is important to predict prognosis. A diagnostic procedure is necessary if another diagnosis is being considered. Management of SJS-TEN includes cessation of suspected drugs, early treatment such as fluid resuscitation, early nutrition, treatment and evaluation of eyes and skin lesions. Multiorgan involvement can occur in SJS-TEN so multidisciplinary management is needed for optimal therapy. Corticosteroids and cyclosporin A provide beneficial effects on SJS-TEN. SCORTEN is used to evaluate prognosis.